Arbuscular mycorrhizal fungi association and root rot disease in mungbean (Vigna radiata) growing areas of Haryana - SARAN, MAHENDRA KUMAR; CHUGH, RAKESH KUMAR; RAJ, KUSHAL; MEHTA, SATISH KUMAR; YADAV, PANKAJ; KUMARI, DEEPAK (The Indian Journal of Agricultural Sciences, 2024)
The study was carried out during rainy (kharif) seasons of 2021 and 2022 at Chaudhary Charan Singh Haryana Agricultural University, Hisar, Haryana to provide a comprehensive understanding of how the presence and activity of arbuscular mycorrhizal (AM) fungi may influence the development of root rot in mungbean (Vigna radiata L.) crops in different mungbean-growing areas of Haryana. Root colonization by AM fungi in Hisar, Bhiwani, Mahendragarh, and Charkhi Dadri districts of Haryana ranged from 16.45 to 24.07%, 7.71 to 16.73%, 7.02 to 21.43% and 7.59 to 22.28%, respectively. This variability underscores the diverse interactions between mungbean plants and AM fungi in these distinct geographical regions, reflecting the influence of environmental factors and local soil conditions on mycorrhizal associations. Sporocarp numbers in these districts ranged from 76.5 to 131.5, 37 to 102, 54 to 119.5 and 65.5 to 118 per 100 g of soil, respectively. These findings emphasize the dynamic nature of AM fungal populations and their potential impact on the overall soil health and plant-microbe interactions in mungbean cultivation. Similarly, root rot incidence in these districts varied from 6.59 to 11.62%, 7.48 to 11.29%, 7.05 to 11.43% and 5.88 to 11.76%, while root rot intensity ranged from 2.77 to 4.82%, 2.70 to 4.61%, 2.06 to 4.61% and 2.43 to 4.85% in Hisar, Bhiwani, Mahendragarh, and Charkhi Dadri districts, respectively. This variability in root rot incidence and intensity highlights the susceptibility of mungbean crops to this detrimental disease and emphasizes the importance of region-specific strategies for disease management.